Neural Basis of Extremely High Temporal Sensitivity: Insights From a Patient With Autism - Ide, Masakazu; Atsumi, Takeshi; Chakrabarty, Mrinmoy; Yaguchi, Ayako; Umesawa, Yumi; Fukatsu, Reiko; Wada, Makoto (Frontiers in Neuroscience, 2020)
The human brain is sensitive to incoming sensory information across multiple time scales. Temporal scales of information represented in the brain generally constrain behaviour. Despite reports of the neural correlates of millisecond timing, how the human brain processes sensory stimuli in the sub-second range (≤ 100 milliseconds) and its behavioural implications are areas of active scientific enquiry. An autism spectrum disorder (ASD) patient showed a tactile discrimination threshold of 6.49 ms on a temporal order judgement task (TOJ) which was approximately 10 folds superior than other ASD and healthy controls (59 and 69 ms, respectively). To investigate the brain regions of this extremely high temporal resolution in T.R, we used functional magnetic resonance imaging (fMRI) during TOJ. We observed greater activity notably in the left superior temporal gyrus (STG) and precentral gyrus (PrG) compared to that of controls. Generally, the left superior frontal gyrus (SFG) correlated positively, while the opercular part of right inferior frontal gyrus (IFG) correlated negatively, with the correct TOJ rate across all subjects (T.R. + 22 healthy controls). We found the performance was negatively correlated with the strength of neural responses in the right IFG overall in 30 participants (T.R. + 22 healthy and 7 ASD controls). Our data reveal superior ability of this particular case of ASD in the millisecond scale for sensory inputs. We highlight several neural correlates of TOJ underlying the facilitation and / or inhibition of temporal resolution in humans.